Development of an alternative rework process for ceramic ball grid array 256 (CBGA256) assembly - Chua, Kai Meng. (2009)
In the assembly of ceramic ball grid array (CBGA) packages to a printed circuit board, various factors could affect the functionality of the package. A rework operation which removes and replaces the defective component is thus required. However, the deficiency of the site preparation has become the bottleneck among the existing rework processes. Furthermore, the reliability of the existing rework processes is not available. In this project, an alternative rework process was proposed and developed; and its reliability was investigated through temperature cycling from -40°C to +125°C. The reliability of the prime (not reworked) assembly and a commonly used rework process was also included in the assessment. Electrical resistance was continuously monitored during the life time of the test to detect any failure. Some samples were cross-sectioned after a number of temperature cycles and examined under scanning electronic microscope (SEM), for understanding the failure mechanism. Crack initiation and propagation were observed and analysed. Examination of the samples after 500 temperature cycles revealed that cracks were initiated at the outer rows of the array of solder joints in the packages. The cracks occurring near the interface between the solder and the ceramic had been identified as the main cause of final package failure. In this work the feasibility of the proposed rework process has been demonstrated. In addition, the reworked solder joints were found to be highly reliable. The projected service life of a reworked CBGA at 50% failure for automobile application was estimated to be 38 years.